Penerapan Reciprocal Teaching melalui Lesson Study untuk Meningkatkan Hasil Belajar Kognitif Mahasiswa pada Matakuliah Biologi Umum Universitas Negeri Malang Tahun Pelajaran 2014/2015 - Umi Nurjanah (Pendidikan Biologi,Universitas Islam Jember, 2017)
Achievement of targeted learning in the course must be in accordance with the competence of graduates specified in the Indonesian National Qualification Framework (KKNI), so that to make it happen required learning methods that can build the competence. The result of observation, the students are still less uniform in the mastery of proven concepts in the discussion and question and answer are not many who convey the idea of understanding. Based on the observations need to apply Reciprocal Teaching (RT) through Lesson study (LS). The purpose of this research is to know the improvement of students' cognitive learning outcomes and the implementation of RT teaching methods through LS. The sample used in this research is the students of State University of Malang Semester III Offering C-C and C-F with the number of students 31 people, consisting of 3 men and 28 women. Application of Reciprocal Teaching through LS is implemented for 3 LS cycles, each cycle consisting of plan, do and see stages. The results showed that the learning of Reciprocal Teaching through LS able to increase the average of cognitive learning result of student equal to 84,35 with 100% classical completeness. The implementation of the LS RT-based learning works very well. Keywords: Reciprocal Teaching, Lesson Study, learning outcomes